A novel species of Hyalorbilia (Orbiliaceae, Orbiliales) from Thailand - Yuan, Lingling; Chethana, K.w. Thilini; Thiyagaraja, Vinodhini; Luo, Le; Hyde, Kevin D.; Zhao, Qi (Phytotaxa, 2026)
Hyalorbilia, a genus in the family Orbiliaceae (Orbiliales), currently accommodates 45 species, including three recorded from Thailand: H. arcuata Baral, M.L. Wu & Y.C. Su, H. erythrostigma (W. Phillips) Baral & G. Marson, and H. inflatula (P. Karst.) Baral & G. Marson. This study reports a new Hyalorbilia species from Thailand, identified on the basis of both morphological characteristics and multi-locus phylogenetic analyses. Our new species, Hyalorbilia chiangmaiensis, is distinguished from other Hyalorbilia species by its strongly curved, sickle-shaped ascospores in the living state, and less strongly curved, spindle- to rod-shaped, aseptate ascospores in the dead state, with shrunken ends that are never distinctly helicoidal. The present study provides a detailed description, illustrations, and a comparison to the closely associated species in this genus.